Poly(3-hydroxypropionate): Biosynthesis Pathways and Malonyl-CoA Biosensor Material Properties - Aduhene, Albert Gyapong; Cui, Hongliang; Yang, Hongyi; Liu, Chengwei; Sui, Guangchao; Liu, Changli (Frontiers in Bioengineering and Biotechnology, 2021)
Many single-use non-degradable plastics are a threat to life today, and several polyhydroxyalkanoates (PHAs) biopolymers have been developed in the bioplastic industry to place petrochemical-based plastics. One of such is the novel biomaterial poly(3-hydroxypropionate) [poly(3HP)] because of its biocompatibility, biodegradability, and high yield synthesis using engineered strains. To date, many bio-polymer-based functional composites have been developed to increase the value of raw microbial-biopolymers obtained from cheap sources. This review article broadly covers poly(3HP), a comprehensive summary of critical biosynthetic production pathways comparing the yields and titers achieved in different Microbial cell Factories. This article also provides extensive knowledge and highlights recent progress on biosensors' use to optimize poly(3HP) production, some bacteria host adopted for production, chemical and physical properties, life cycle assessment for poly(3HP) production using corn oil as carbon source, and some essential medical applications of poly(3HP).